The role of vascular endothelial growth factor isoforms in early follicle development - McFee, Renee Marie (Kansas State University, 2012)
Since vascularization of the theca layer increases as follicles progress in size through preantral and antral stages, the principal angiogenic factor, vascular endothelial growth factor A (VEGFA), may influence follicle growth via regulation of angiogenesis. However, VEGFA may also influence follicular development through nonangiogenic mechanisms since its expression has been localized to nonvascular follicles and cells. Alternative mRNA splicing of 8 exons from the VEGFA gene results in the formation of different VEGFA isoforms. Each isoform has unique properties and is identified by the number of amino acids within the mature protein. Proangiogenic isoforms are encoded by exon 8a while a sister set of isoforms with antiangiogenic properties are encoded by exon 8b. The antiangiogenic isoforms comprise the majority of VEGFA expressed in most tissues while expression of the proangiogenic VEGFA isoforms is upregulated in tissues undergoing active angiogenesis. The Vegfa angiogenic isoforms (Vegfa_120, Vegfa_164, and Vegfa_188) were detected in developing rat ovaries, and quantitative RT-PCR determined that Vegfa_120 and Vegfa_164 mRNA was more abundant after birth, while Vegfa_188 mRNA was highest at embryonic day 16. The antiangiogenic isoforms, Vegfa_165b and Vegfa_189b, were amplified and sequenced from rat ovaries and quantitative RT-PCR determined that Vegfa_165b mRNA was more abundant around embryonic day 18, but Vegfa_189b lacked a distinct pattern of abundance. VEGFA and its receptors were localized to pregranulosa and granulosa cells of all follicle stages and to theca cells of advanced-stage follicles. Antiangiogenic VEGFA isoforms were localized to pregranulosa and granulosa cells of all follicle stages and to theca cells of advanced-stage follicles. To determine the role of VEGFA in developing ovaries, postnatal day 3/4 rat ovaries were cultured with VEGFR-TKI, a tyrosine kinase inhibitor that blocks signaling through the VEGFA receptors, FLT1 and KDR. Ovaries treated with VEGFR-TKI had vascular development reduced by 94%. In addition, treated ovaries had more primordial follicles, fewer early primary, transitional, and secondary follicles, and greater total follicle numbers compared with control ovaries. This suggests that VEGFA promotes follicle recruitment and early follicular development. These effects may be dependent upon increased ovarian vascularization or they may be mediated by nonvascular mechanisms.
Keywords: Ovary; Follicle; VEGFA; Isoforms; Physiology (0719)